Potensi Produk Cair (Oil Phase dan Water Phase) Pirolisis Mikroalga Sebagai Pengawet Makanan - Siti Jamilatun; Martomo Setyawan; Ilham Mufandi; Arief Budiman (Universitas Ahmad Dahlan, 2019)
Microalgae is one of the oldest living organisms namely Thallophyta (plant lacking roots, stems, and leaves) that have chlorophyll as a pigment to mainly photosynthesis process. Microalgae as the water plant had some characteristics such as high carbohydrate, protein, and lipid content in which can be produced energy (liquid, solid, and gas) by using the pyrolysis process. The raw material in this experiment was used Spirulina platensis as the type of microalgae. The residue of Spirulina platensis was content acid, phenol, dan carbonyl in which this product liquid is potential as a food preservative. The experiment was performed by using the pyrolysis process which is equipped with a cooler (condenser) to condense the combustion vapor. Thermal decomposition was conducted in the pyrolysis reactor with a temperature of 300 ℃, 400 ℃, 500 ℃, and 600 ℃ under atmospheric condition. The result indicated that the pyrolysis proses had oil phase as the top result and water phase as the bottom result. The result from GC/MS analysis reported that the pyrolysis process on temperature of 300 ℃ can produce the oil phase with the phenol content of 6.7 wt.%, acid of 33.03 wt.%, carbonyl of 4.95 wt.%, and Poly Aromatic Hydrocarbon (PAH) of 6.23 wt.%, respectively. Otherwise, the pyrolysis process can produce the water phase (liquid smoke) on temperature 400 °C, 500 °C, dan 600 °C with the phenol content of 0.22 wt.%, acid content of 0.69-9.12 wt.%, carbonyl content of 10.46-13.02 wt.% and PAH of 26.93-45.18 wt.%. The superiority of preservatives from residual Spirulina platensis has a high nitrogenate content from protein decomposition (10.13-31.22 wt.%). High protein content in food preservatives can be used as an additive compound to increase protein intake.